PKM KELOMPOK TERNAK LEBAH MADU (APIS CERANA) DALAM PENINGKATAN KESEJAHTERAAN KELOMPOK DI DESA BAHA - I Made Subrata; I Dewa Putu Juwana; I Made Surat; I Wayan Sumandya (LP3M Universitas PGRI Mahadewa Indonesia, 2023)
Apis cerana is a local Asian bee that is distributed almost throughout this continent. Apis cerana is a type of local honey bee that is prone to migration when natural food sources are insufficient. Based on the results of discussions with members of the honey bee group in Baha village, a priority problem that needs to be addressed by group members with assistance from universities can be formulated, namely increasing the ability of group members to be able to adopt appropriate technology for developing honey bees according to required standards so that productivity increases. Adopting technology to reduce mortality rates by using artificial feed. The queen rearing method is used to produce honey bees with high productivity and can carry out post-harvest technology if enough product is produced. The solution offered is to hold outreach. The counseling material concerns: how to develop appropriate, cheap and easy management techniques and develop Apis cerana honey bees, this problem will be informed to honey bee breeders in Baha village, Mengwi sub-district, Badung Regency. Efforts to increase the reproduction and productivity of bees, the application of alternative technology includes the selection of superior seeds and the use/operation of extractor machines in an effort to increase the productivity of bees with their support poles to avoid pests, and how to formulate honey bee animal feed that is cheap, easy to obtain and available in the village. according to livestock needs. After the counseling was carried out, training was carried out for the two groups using three students, such as making colony boxes with supporting poles to avoid pests and diseases of the Apis cerana honey bee.